67-45 State Street, ca. 1870 - Unknown (Tufts Archival Research Center, 2005)
Street-level view east-southeast of (left to right) 67-45 State Street, located between Kilby Street to the east-northeast and Congress Street to the west-southwest. Signage adorns the facades of the buildings, which face north-northwest. The columned-facade of the Boston Exchange Company Building, located at 49-57 State Street, is included in the center of the photograph. Street lamps line the sidewalk, and several men stand in front of the buildings. Two horse-drawn wagons are parked along the curb in front of the Boston Exchange Company Building. 8 1/8 x 6 1/16, 10 1/8 x 7 9/16 overall Photographs